2005
DOI: 10.1682/jrrd.2005.01.0006
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and aging: New research findings and clinical implications

Abstract: This review provides an overview of recent research that addressed hearing loss and auditory processing problems among elderly people. It focuses on research from the University of Maryland on problems in auditory temporal processing by elderly listeners as assessed in speech perception experiments using temporally altered signals and in psychoacoustic experiments of duration and rhythm discrimination for simple and complex signals. Some recent studies of perceived hearing disability are also reviewed. The cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(193 citation statements)
references
References 67 publications
(82 reference statements)
7
182
1
3
Order By: Relevance
“…A number of studies have shown that hearing loss among diabetics predominantly involves the high frequencies. 7,8 This is similar to presbyacusis, that affects higher frequencies first. 9,10 Sensory hair cell loss and cochlea neuron loss at the basal turns are thought to be responsible for presbyacusis.…”
Section: Introductionmentioning
confidence: 60%
“…A number of studies have shown that hearing loss among diabetics predominantly involves the high frequencies. 7,8 This is similar to presbyacusis, that affects higher frequencies first. 9,10 Sensory hair cell loss and cochlea neuron loss at the basal turns are thought to be responsible for presbyacusis.…”
Section: Introductionmentioning
confidence: 60%
“…It has been found that speech recognition performance of older adults even with normal hearing, especially in presence of noise, is reduced to greater extent in older adults than compared to young adults. It happens probably due to greater auditory temporal processing deficits (Mattys et al, 2012;Pichora-Fuller & Souza, 2003;Gordon-Salant, 2005;Pichora-Fuller & Singh, 2006). Other factors such as widening of auditory filters also may lead to worsened speech perception with presbycusis (Saremi and Stenfelt, 2013).…”
Section: Agingmentioning
confidence: 99%
“…Commonly, when talking about older people, older adults and elderly, this refers to individuals over the age of 65 (Gordon-Salant, 2005;Gorman, 1999;Roebuck, 1979). This also applies for this present thesis.…”
Section: Hearing Loss Cognition and Agingmentioning
confidence: 93%